Sarcopenia and cognitive performance in hospitalized older adults: evidence of an association - Simili, Otávio Augusto Garcia; Garcia, Lorena Natalino Haber; Sollis, Caroline; Barbalho, Sandra Maria; Bechara, Marcelo Dib; Lamas, Caroline Barbalho; Detregiachi, Claudia Rucco Penteado; Quesada, Karina (Frontiers in Dementia, 2026)
IntroductionPopulation aging increases the coexistence of geriatric syndromes, including sarcopenia and cognitive impairment, which negatively affect functional prognosis and clinical outcomes. Evidence on the association between sarcopenia and cognitive performance in hospitalized elderly individuals, particularly across cognitive domains, remains limited. Therefore, the objective of this study was to investigate the association between sarcopenia and cognitive performance, both globally and across specific cognitive domains, in hospitalized elderly individuals.MethodsThis observational cross-sectional study included elderly patients hospitalized in a medium-sized hospital in São Paulo, Brazil, from 2024 to 2025, evaluated within the first 48 hours of admission. Exclusion criteria included weight-loss diets, chronic renal failure on dialysis, paresis or hemiparesis due to stroke, altered body fluid levels, pacemaker use, and chronic corticosteroid therapy. Sarcopenia screening and diagnosis followed the European Consensus criteria, and cognitive performance was assessed using the Mini-Mental State Examination (MMSE). Comparative analyses were conducted among non-sarcopenic, sarcopenia risk, and sarcopenic groups, including correlations with sociodemographic variables.ResultsEighty-four older adults were assessed (54.76% women; mean age 68.1 ± 6.7 years). Sarcopenia risk was identified in 29.76% and confirmed sarcopenia in 19.05%. MMSE scores showed a moderate negative correlation with age (r = −0.48; p < 0.0001) and positive correlations with education (r = 0.58; p < 0.0001), physical activity (r = 0.31; p = 0.0038), and income (r = 0.23; p = 0.0326). Mean MMSE scores differed significantly among groups: non-sarcopenic (26.84 ± 3.24), sarcopenia risk (22.32 ± 5.86), and sarcopenic (18.69 ± 7.98) (p < 0.0001). Worse performance in orientation, attention/calculation, and language was observed in the sarcopenia risk and sarcopenia groups (p < 0.001).ConclusionSarcopenia, even at early stages, is associated with reduced global cognitive performance and specific impairments in orientation, attention/calculation, and language in hospitalized elderly individuals. These findings underscore the importance of early screening and targeted interventions to preserve both muscle and cognitive health, reinforcing the need for integrated care strategies in hospital settings.